Design of experiments applied to lithium-ion batteries: A literature review. (15th August 2022) - Román-Ramírez, L.A.; Marco, J.
Highlights: The Design of Experiments methodology and statistical analysis is introduced. Design of experiments is a valuable tool for the design and development of lithium-ion batteries. Critical review of Design of Experiments applied to different aspects of lithium-ion batteries. Ageing, capacity, formulation, active material synthesis, electrode and cell production, thermal design, charging and parameterisation are covered. Abstract: The statistical design of experiments methodology (DoE) has been a valuable tool since its conception for the understanding of the relationship between factors and responses. Although it has been employed successfully in different research fields and industries for years, its application to the evaluation of lithium-ion batteries (LIBs) is just getting recognition. LIBs are one of the most promising technologies for a complete transition to sustainable energies, are the main technology behind electric vehicles and are fundamental for the continual development of portable electronic devices. This paper presents a critical literature review of the available DoE works applied to the manufacturing and characterisation of LIBs. An overview of DoE and the most important available designs are first presented, followed by a general introduction of the statistical analysis required for the interpretation of the results including regression models. Several aspects of the LIBs such as ageing, capacity, electrode formulation, active material synthesis, thermal design, charging and parameterisation are discussed based on the main objective of the respective DoE studies found in the literature. A case study is presented to visualise the practical application of DoE to the LIBs field. Perspectives and future outlook are given to highlight opportunities and potential areas of research in the application of traditional and modern designs to the LIB's field. This critical review contributes to a better understanding of the DoE methodology with a focus on LIBs or LIBs related aspects which will lead to faster developments in the field.